2020
DOI: 10.1097/inf.0000000000002993
|View full text |Cite
|
Sign up to set email alerts
|

Benzylpenicillin Serum Concentrations in Neonates With Group B Streptococci Sepsis or Meningitis

Abstract: Background: Adequate dosage recommendations are imperative for successful treatment of invasive infections. We evaluated the occurrence of sub-and supratherapeutic serum and cerebrospinal fluid (CSF) concentrations of benzylpenicillin (BPEN) in neonates treated for a severe group B streptococci (GBS) sepsis and/or meningitis as well as discrepancies in dosing recommendations provided by pediatric reference sources. Methods: Retrospective analysis of (pre)term infants treated with BPEN undergoing therapeutic dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The study characteristics of the 16 observational studies included are shown in Table S2. These studies investigated a number of different populations including: paediatric critically ill patients, 39 critically ill patients, 36,37,[40][41][42][43][44][45] critically ill patients with alternate renal functions such as receiving continuous RRT, 46 or augmented renal clearance, 47 patients treated for specific infections, 48,49 and burns patients. 38,50 The majority of studies (11/16, 69%) included non-penicillin antibiotics with analyses not separating outcomes for individual antibiotics.…”
Section: Study Characteristics and Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The study characteristics of the 16 observational studies included are shown in Table S2. These studies investigated a number of different populations including: paediatric critically ill patients, 39 critically ill patients, 36,37,[40][41][42][43][44][45] critically ill patients with alternate renal functions such as receiving continuous RRT, 46 or augmented renal clearance, 47 patients treated for specific infections, 48,49 and burns patients. 38,50 The majority of studies (11/16, 69%) included non-penicillin antibiotics with analyses not separating outcomes for individual antibiotics.…”
Section: Study Characteristics and Resultsmentioning
confidence: 99%
“…Another common feature (in 9/16 studies, 56%) was the inclusion of concomitant antibiotics in the regimen, with the majority having no analysis of the impact of this on clinical outcomes. 36,39,40,42,[47][48][49]51 A key component of TDM is adjustment of doses to improve target drug level attainment and this was shown to be successful in a number of studies. [38][39][40]43,46,49 However, in others the effectiveness of dose adjustment was either not assessed 37,45,47,50 or was shown to be ineffective.…”
Section: Study Characteristics and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…124 One good example for this could be beta-lactams as recent studies have shown that in neonates with sepsis therapy failure, as little as 20% of the benzyl penicillin concentrations were within the target range. 125 MONITORING SEPSIS COURSE Assessing treatment effect LONS may compromise the cardiovascular system, leading to reduced cardiac output and/or disturbed microcirculation, but also other organ systems. Adequate biomarkers to judge effectiveness of LONS management would significantly improve clinical care; knowing you are on the right track even before the patient shows clinical recovery, potentially prevents overuse of supportive therapy and unnecessary switches to broad-spectrum antibiotics.…”
Section: Pks Of Antibioticsmentioning
confidence: 99%